US, EU, and Japanese Regulatory Guidelines for Development of Drugs for Treatment of Alzheimer's Disease: Implications for Global Drug Development - Anne Vinther Morant; Henrik Tang Vestergaard; Anders Blædel Lassen; Vaidrius Navikas (Wiley, 2020)
Drug development guidelines from regulatory authorities provide important information to sponsors on requirements for clinical evidence needed to support approval of new drugs. In the field of Alzheimer's disease (AD), recently published guidelines are available from EU, US, and Japanese regulatory authorities. In this review, these three guidelines are compared and discussed with emphasis on the recommendations provided for demonstration of efficacy in pivotal clinical trials conducted in predementia stages of AD. Similarities and differences are highlighted, and impact for global drug development is discussed in the context of the new International Conference on Harmonization E17 guideline on multiregional clinical trials. The AD field is characterized by significant challenges as, to date, no drug approval precedence exists in predementia AD despite numerous and ambitious efforts to slow the progression of the disease by pharmacologic intervention. Despite these uncertainties regulatory authorities across regions have blazed a trail for proactive multistakeholder collaboration, involvement, and continuous dialogue, setting a positive example on how to foster a supportive environment for development of new and meaningful treatments for patients with AD globally.